Novel historic building repairing and caulking inorganic glue and preparation method thereof
By adding regenerated fine aggregate and glutinous rice flour to magnesium phosphate inorganic adhesive, magnesium phosphate regenerated inorganic adhesive is prepared, which solves the problem of the degradation of traditional glutinous rice mortar in low temperature environments, and achieves efficient and durable joint filling effect in the restoration of ancient buildings in cold areas, and reduces carbon emissions.
Patent Information
- Application Number
- CN202510027260.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-03-21
AI Technical Summary
Traditional glutinous rice mortar shows degradation in low temperature environments, including weakening of adhesion and increased brittleness, which makes it difficult to meet the needs in the restoration of ancient buildings in cold areas.
A new type of ancient building restoration and caulking inorganic glue is used to prepare magnesium phosphate regenerated inorganic glue by adding regenerated fine aggregate and glutinous rice flour to the magnesium phosphate inorganic glue. The composition of the inorganic glue includes refired magnesium oxide, potassium dihydrogen phosphate, borax, fine aggregate, basalt fiber, glutinous rice flour and water. Through specific ratios and preparation methods, a colloid with excellent bonding effect and durability is formed.
The new inorganic adhesive exhibits good durability, excellent bonding effect, fast hardness, early strength and high strength in low temperature environments. At the same time, compared with traditional inorganic adhesives, it can effectively reduce carbon emissions.
Smart Images

Figure CN119661185A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of inorganic adhesive technology, specifically, it relates to a novel inorganic adhesive for filling cracks in the repair of ancient buildings and its preparation method. Background Technology
[0002] Ancient architecture is an important part of the cultural heritage of the Chinese nation, carrying rich historical, cultural, and artistic value. However, over time, ancient buildings have suffered varying degrees of damage and aging due to natural factors (such as weathering, erosion, and earthquakes) and human factors (such as war and urbanization). Especially in cold regions, the restoration of ancient buildings faces unique challenges. Due to the influence of cold climates, ancient buildings are more susceptible to damage from natural factors such as freeze-thaw cycles and weathering, increasing the difficulty of restoration. Furthermore, the special climatic conditions of cold regions place higher demands on the performance of restoration materials. Traditional restoration materials may experience performance degradation in low-temperature environments, such as weakened adhesion and increased brittleness, which may affect the durability of the restoration results.
[0003] In ancient times, glutinous rice mortar was widely used in construction, such as in city walls, bridges, temples, and palaces. It was not only used for bricklaying but also for filling gaps between bricks and stones to enhance the strength and durability of buildings. With its unique bonding strength and durability, it has held an important place throughout history. Currently, there are many materials available for filling gaps in the repair of ancient buildings, but there are few reports on the use of glutinous rice flour in such mortars. Studies have shown that traditional glutinous rice mortar, when used alone, experiences longer setting times and reduced fluidity at low temperatures (-20℃ to -5℃), resulting in decreased mechanical and workability. Therefore, the long-term service temperature of traditional glutinous rice mortar should not be lower than -5℃; when the temperature drops to -30℃, traditional glutinous rice mortar completely loses its workability.
[0004] In extreme weather conditions, ambient temperatures can be extremely low. Traditional grouting materials for ancient building repair are completely inadequate to meet current needs, while modified low-temperature resistant repair materials are relatively uneconomical, limiting their development. Therefore, this invention proposes a novel inorganic adhesive for ancient building repair and its preparation method to solve the problems existing in the prior art. Summary of the Invention
[0005] The technical problem to be solved by the present invention is to overcome the shortcomings of the prior art and provide a new type of inorganic adhesive for filling gaps in the repair of ancient buildings and its preparation method, thereby solving the problems mentioned in the background art.
[0006] To solve the above-mentioned technical problems, the basic concept of the technical solution adopted by the present invention is as follows:
[0007] A novel inorganic adhesive for caulking joints in the restoration of ancient buildings comprises the following components by weight:
[0008] The composition comprises 30-48 parts of recalcined magnesium oxide, 20-30 parts of potassium dihydrogen phosphate, 2-6 parts of borax, 6-24 parts of fine aggregate, 3-8 parts of basalt fiber, 5-15 parts of glutinous rice flour, and 15-20 parts of water. The recalcined magnesium oxide is one or a mixture of MgO, Al2O3, Fe2O3, CaO, SO2, TiO2, Na2O, and SO3. The fine aggregate is a mixture of recycled fine aggregate with a particle size of 2-5 mm and ceramsite at a mass ratio of 2.8-3.7:2.2-3.1. The recycled fine aggregate is one of glass powder, recycled stone powder, recycled brick powder, and recycled cement. The recycled stone powder is obtained by grinding and sieving recycled stone powder to a fineness of 600-700 mesh.
[0009] A method for preparing a novel inorganic adhesive for caulking joints in ancient building restoration includes the following steps:
[0010] Step 1: Weigh all materials according to the raw material ratio. Then, pour potassium dihydrogen phosphate, fine aggregate, glutinous rice flour, basalt fiber, and borax into a cement mortar mixer and dry mix for 0.5-2 minutes. Next, slowly add 1 / 3-3 / 4 of the total water volume and continue mixing to obtain a uniform slurry. Specifically, the preparation of potassium dihydrogen phosphate involves adding 4-8 mol / L phosphoric acid to a round-bottom flask, then using a glass rod to guide the pouring of 200-300 ml of 4-8 mol / L potassium hydroxide. The mixture is then heated under reflux at 300-500℃ to generate a precipitate. The precipitate is then filtered, and the filtrate is concentrated to 1.3-1.3 ppm. The relative density is 5. After cooling and filtration to remove crystals, the crystals are washed with deionized water and dried to obtain potassium dihydrogen phosphate. The preparation of basalt fiber involves placing 10-15g of basalt rock material in a calcining furnace and placing it at 1450℃-1500℃ for 5-15 minutes. After the basalt rock material melts, it is drawn at high speed using a platinum-rhodium alloy spinneret to obtain continuous basalt fiber. The preparation of glutinous rice flour involves first placing 20-40g of glutinous rice in a grinder, rotating it clockwise for 20-40 minutes, then counterclockwise for 20-40 minutes to obtain glutinous rice flour. Finally, it is passed through an 80-100 mesh sieve to obtain glutinous rice flour.
[0011] Step 2: Then add the recalcined magnesium oxide and the remaining 1 / 4-2 / 3 of the water, stir rapidly for 3-4 minutes, and discharge to obtain magnesium phosphate regenerated inorganic adhesive. Specifically, the preparation of recalcined magnesium oxide involves first calcining magnesite in a kiln at 1500-1900℃, then grinding the calcined material into brownish-yellow granules of different particle sizes, and finally sieving to retain powder with a particle size ≤15mm to obtain recalcined magnesium oxide. Magnesite is a mineral with MgCO3 as its main component, containing ≤0.83% mud, ≤0.4% clay lump, ≤10.0% soundness index, ≤1.0% light matter content, and ≤1.0% sulfide and sulfate content.
[0012] By adopting the above technical solution, the present invention has the following beneficial effects compared with the prior art. Of course, any product implementing the present invention does not necessarily need to achieve all of the following advantages at the same time:
[0013] The present invention relates to a magnesium phosphate recycled inorganic adhesive prepared by incorporating recycled fine aggregate and glutinous rice flour into magnesium phosphate inorganic adhesive. This adhesive has the advantages of low temperature resistance, good durability, excellent bonding effect, rapid hardening, early strength and high strength. At the same time, compared with traditional inorganic adhesives, the magnesium phosphate recycled inorganic adhesive of the present invention can effectively reduce carbon emissions.
[0014] The specific embodiments of the present invention will now be described in further detail with reference to the accompanying drawings. Attached Figure Description
[0015] The accompanying drawings described below are merely some embodiments. Those skilled in the art can obtain other drawings based on these drawings without any creative effort.
[0016] In the picture:
[0017] Figure 1 This is a flowchart of the preparation method of the present invention.
[0018] Figure 2 This is an X-ray diffraction analysis diagram of the magnesium phosphate regenerated inorganic adhesive of the present invention.
[0019] Figure 3 This is a SEM image of the magnesium phosphate regenerated inorganic adhesive reinforced with different fibers according to the present invention.
[0020] Figure 4 This is a SEM image of the borax-reinforced magnesium phosphate regenerated inorganic adhesive of the present invention.
[0021] Figure 5 SEM images of magnesium phosphate regenerated inorganic adhesive used for repairing cracks in ancient buildings at different temperatures.
[0022] Figure 6 This is a SEM image of the glutinous rice paste enhanced with glutinous rice mortar according to the present invention.
[0023] Figure 7 This is a flowchart illustrating the workflow for repairing cracks in ancient buildings according to the present invention.
[0024] It should be noted that these accompanying drawings and textual descriptions are not intended to limit the scope of the invention in any way, but rather to illustrate the concept of the invention to those skilled in the art by referring to specific embodiments. Detailed Implementation
[0025] The invention will now be described in further detail with reference to the accompanying drawings.
[0026] Example 1: Please refer to Figure 1-7 As shown, this embodiment provides a novel inorganic adhesive for repairing and filling cracks in ancient buildings, comprising the following components by weight:
[0027] The composition comprises 30-48 parts of recalcined magnesium oxide, 20-30 parts of potassium dihydrogen phosphate, 2-6 parts of borax, 6-24 parts of fine aggregate, 3-8 parts of basalt fiber, 5-15 parts of glutinous rice flour, and 15-20 parts of water. The recalcined magnesium oxide is one or a mixture of MgO, Al2O3, Fe2O3, CaO, SO2, TiO2, Na2O, and SO3. The fine aggregate is a mixture of recycled fine aggregate with a particle size of 2-5 mm and ceramsite at a mass ratio of 2.8-3.7:2.2-3.1. The recycled fine aggregate is one of glass powder, recycled stone powder, recycled brick powder, and recycled cement. The recycled stone powder is a powder with a fineness of 600 mesh obtained by grinding and sieving recycled stone powder.
[0028] The present invention relates to a magnesium phosphate recycled inorganic adhesive prepared by incorporating recycled fine aggregate and glutinous rice flour into magnesium phosphate inorganic adhesive. This adhesive has the advantages of low temperature resistance, good durability, excellent bonding effect, rapid hardening, early strength and high strength. At the same time, compared with traditional inorganic adhesives, the magnesium phosphate recycled inorganic adhesive of the present invention can effectively reduce carbon emissions.
[0029] Example 1.1: A novel inorganic adhesive for repairing and filling joints in ancient buildings, comprising the following components by weight:
[0030] Cementitious material dosage: 48% magnesium oxide, 25% potassium dihydrogen phosphate, and 3% basalt fiber; admixture dosage: 5% borax and 19% water.
[0031] Example 1.2: A novel inorganic adhesive for repairing and filling joints in ancient buildings, comprising the following components by weight:
[0032] Cementitious material dosage: 46% magnesium oxide, 25% potassium dihydrogen phosphate, and 5% basalt fiber. Admixture dosage: 5% borax and 19% water.
[0033] Example 1.3: A novel inorganic adhesive for repairing and filling joints in ancient buildings, comprising the following components by weight:
[0034] Cementitious material dosage: 43% magnesium oxide, 25% potassium dihydrogen phosphate, and 8% basalt fiber. Admixture dosage: 5% borax and 19% water.
[0035] Example 1.4: A novel inorganic adhesive for filling joints in ancient building repairs, comprising the following components by weight:
[0036] Grind the recycled stone powder in a grinder to 0.5-1 μm for later use; Cementitious material dosage: 40% magnesium oxide, 8% recycled stone powder, 25% potassium dihydrogen phosphate, and 3% basalt fiber. Admixture dosage: 5% borax and 19% water.
[0037] Example 1.5: A novel inorganic adhesive for filling joints in ancient building repairs, comprising the following components by weight:
[0038] Grind the recycled stone powder in a grinder to 0.5-1 μm for later use; Cementitious material dosage: 36% magnesium oxide, 12% recycled stone powder, 25% potassium dihydrogen phosphate, and 3% basalt fiber. Admixture dosage: 5% borax and 19% water.
[0039] Example 1.6: A novel inorganic adhesive for filling joints in ancient building repairs, comprising the following components by weight:
[0040] Grind the recycled stone powder in a grinder to 0.5-1 μm for later use; Cementitious material dosage: 33% magnesium oxide, 15% recycled stone powder, 25% potassium dihydrogen phosphate, and 3% basalt fiber. Admixture dosage: 5% borax and 19% water.
[0041] Example 1.7: A novel inorganic adhesive for repairing and filling joints in ancient buildings, comprising the following components by weight:
[0042] Grind the recycled stone powder in a grinder to 0.5-1 μm for later use; Cementitious material dosage: 26% magnesium oxide, 24% recycled stone powder, 25% potassium dihydrogen phosphate, and 3% basalt fiber. Admixture dosage: 5% borax and 19% water.
[0043] Example 1.8: A novel inorganic adhesive for repairing and filling joints in ancient buildings, comprising the following components by weight:
[0044] Grind glutinous rice flour in a grinder to 0.5-1µm and set aside. Cementitious materials: 46% magnesium oxide, 2% glutinous rice flour, 25% potassium dihydrogen phosphate, and 3% basalt fiber. Additives: 5% borax and 19% water.
[0045] Example 1.9: A novel inorganic adhesive for filling joints in ancient building repairs, comprising the following components by weight:
[0046] Grind glutinous rice flour in a grinder to 0.5-1µm and set aside. Cementitious materials: 45% magnesium oxide, 3% glutinous rice flour, 25% potassium dihydrogen phosphate, and 3% basalt fiber. Additives: 5% borax and 19% water.
[0047] Example 1.10: A novel inorganic adhesive for filling joints in ancient building repairs, comprising the following components by weight:
[0048] Grind glutinous rice flour in a grinder to 0.5-1µm and set aside. Cementitious materials: 43% magnesium oxide, 5% glutinous rice flour, 25% potassium dihydrogen phosphate, and 3% basalt fiber. Additives: 5% borax and 19% water.
[0049] Example 1.11: A novel inorganic adhesive for filling joints in ancient building repairs, comprising the following components by weight:
[0050] Grind glutinous rice flour in a grinder to 0.5-1µm and set aside. Cementitious materials: 40% magnesium oxide, 8% glutinous rice flour, 25% potassium dihydrogen phosphate, and 3% basalt fiber. Additives: 5% borax and 19% water.
[0051] Example 1.12: A novel inorganic adhesive for filling joints in ancient building repairs, comprising the following components by weight:
[0052] Grind glutinous rice flour in a grinder to 0.5-1µm and set aside. Cementitious materials: 38% magnesium oxide, 10% glutinous rice flour, 25% potassium dihydrogen phosphate, and 3% basalt fiber. Additives: 5% borax and 19% water.
[0053] Example 1.13: A novel inorganic adhesive for repairing and filling joints in ancient buildings, comprising the following components by weight:
[0054] Grind glutinous rice flour in a grinder to 0.5-1µm and set aside. Cementitious materials: 33% magnesium oxide, 15% glutinous rice flour, 25% potassium dihydrogen phosphate, and 3% basalt fiber. Additives: 5% borax and 19% water.
[0055] Example 1.14: A novel inorganic adhesive for filling joints in ancient building repairs, comprising the following components by weight:
[0056] Cementitious material dosage: 30% magnesium oxide, 18% glutinous rice flour, 25% potassium dihydrogen phosphate, and 3% basalt fiber. Admixture dosage: 5% borax and 19% water.
[0057] Example 2: A method for preparing a novel inorganic adhesive for filling joints in ancient building repairs, comprising the following steps:
[0058] Step 1: Weigh all materials according to the raw material ratio. Then, pour potassium dihydrogen phosphate, fine aggregate, glutinous rice flour, basalt fiber, and borax into a cement mortar mixer and dry mix for 1 minute. Next, slowly add 2 / 3 of the total water volume and continue mixing to obtain a uniform slurry. Specifically, the preparation of potassium dihydrogen phosphate involves: first, adding 6 mol / L phosphoric acid to a round-bottom flask, then using a glass rod to guide the pouring of 250 ml of 6 mol / L potassium hydroxide. The mixture is then heated to reflux at 400℃ to generate a precipitate. The precipitate is then filtered, and the filtrate is concentrated to a relative density of 1.32. The process involves: cooling and filtering out the crystals, washing them with deionized water, and drying to obtain potassium dihydrogen phosphate; the preparation of basalt fiber involves placing 12g of basalt rock material in a calcining furnace and placing it at 1450℃-1500℃ for 10 minutes until the basalt rock material melts, then drawing it at high speed using a platinum-rhodium alloy spinneret to obtain continuous basalt fiber; and the preparation of glutinous rice flour involves placing 30g of glutinous rice in a grinder, rotating it clockwise for 30 minutes, then counterclockwise for 30 minutes to obtain glutinous rice flour, and finally passing it through an 80-100 mesh sieve to obtain glutinous rice flour.
[0059] Step 2: Then add the recalcined magnesium oxide and the remaining 1 / 3 of the water and stir rapidly for 3-4 minutes before discharging to obtain magnesium phosphate regenerated inorganic adhesive. Specifically, the preparation of recalcined magnesium oxide involves first calcining magnesite in a kiln at 1700℃, then grinding the calcined material into brownish-yellow granules of different particle sizes, and finally sieving to retain powder with a particle size ≤15mm to obtain recalcined magnesium oxide. Magnesite is a mineral with MgCO3 as its main component, containing ≤0.83% mud, ≤0.4% clay lump, ≤10.0% soundness index, ≤1.0% light matter content, and ≤1.0% sulfide and sulfate content.
[0060] Example 2.1: A method for preparing a novel inorganic adhesive for filling joints in the repair of ancient buildings, specifically as follows:
[0061] Using the gel material from Example 1.1, at room temperature, 2 / 3 of the magnesium oxide and water, along with all of the potassium dihydrogen phosphate, borax, and fibers, were first poured into a mixing pot and stirred for 1 minute. Then, the remaining magnesium oxide and water were added to the mixing pot and stirring continued for 1-2 minutes. Finally, the slurry was poured into a steel mold and allowed to stand for 28 days. This yielded a magnesium phosphate recycled inorganic gelling material used for testing compressive and flexural strength.
[0062] The magnesium phosphate recycled inorganic cementitious material prepared in the example for testing compressive and flexural strength was injected into a 100mm×100mm×100mm steel mold. The measured performance parameters were: flowability 170-180mm, initial setting time 20-25min, final setting time 60-65min, initial compressive strength 69.48-70.11MPa, and initial flexural strength 7.2-7.5MPa.
[0063] Example 2.2: A method for preparing a novel inorganic adhesive for filling joints in the repair of ancient buildings, specifically as follows:
[0064] Using the gel material from Example 1.2, 2 / 3 of the magnesium oxide and water, along with all of the potassium dihydrogen phosphate, borax, and fibers, were first poured into a mixing pot at room temperature and stirred for 1 minute. Then, the remaining magnesium oxide and water were added to the mixing pot and stirring continued for 1-2 minutes. Finally, the slurry was poured into a steel mold and allowed to stand for 28 days. This yielded a magnesium phosphate recycled inorganic gelling material used for testing compressive and flexural strength.
[0065] The magnesium phosphate recycled inorganic cementitious material prepared in the example for testing compressive and flexural strength was injected into a 100mm×100mm×100mm steel mold. The measured performance parameters were as follows: fluidity 135-145mm (too low fluidity), initial setting time 15-20min, final setting time 100-110min (too long final setting time), initial compressive strength 78.03-78.5MPa, and initial flexural strength 11.8-12.0MPa.
[0066] Example 2.3: A method for preparing a novel inorganic adhesive for filling joints in the repair of ancient buildings, specifically as follows:
[0067] Using the gel material from Example 1.3, 2 / 3 of the magnesium oxide and water, along with all of the potassium dihydrogen phosphate, borax, and fibers, were first poured into a mixing pot at room temperature and stirred for 1 minute. Then, the remaining magnesium oxide and water were added to the mixing pot and stirring continued for 1-2 minutes. Finally, the slurry was poured into a steel mold and allowed to stand for 28 days. This yielded a magnesium phosphate recycled inorganic gelling material for testing compressive and flexural strength.
[0068] The magnesium phosphate recycled inorganic cementitious material prepared in the example for testing compressive and flexural strength was injected into a 100mm×100mm×100mm steel mold. The measured performance parameters were as follows: fluidity 135-145mm (too low fluidity), initial setting time 15-20min, final setting time 100-110min (too long final setting time), initial compressive strength 73.24-73.51MPa, and initial flexural strength 10.9-11.6MPa.
[0069] Example 2.4: A method for preparing a novel inorganic adhesive for filling joints in the repair of ancient buildings, specifically as follows:
[0070] Using the gel material from Example 1.4, at room temperature, 2 / 3 of the magnesium oxide and water, along with all of the potassium dihydrogen phosphate, recycled stone powder, borax, and fiber, were first poured into a mixing pot and stirred for 1 minute. Then, the remaining magnesium oxide and water were added to the mixing pot and stirring continued for 1-2 minutes. Finally, the slurry was poured into a steel mold and allowed to stand for 28 days. This yielded a magnesium phosphate recycled inorganic cementitious material for testing compressive and flexural strength.
[0071] The magnesium phosphate recycled inorganic cementitious material prepared in the example for testing compressive and flexural strength was injected into a 100mm×100mm×100mm steel mold, and its performance parameters were measured as follows: fluidity 165-170mm, initial setting time 25-30min, final setting time 75-80min, initial compressive strength reaching 80.2-87.1MPa, and initial flexural strength 8.4-8.9MPa.
[0072] Example 2.5: A method for preparing a novel inorganic adhesive for filling joints in the repair of ancient buildings, specifically as follows:
[0073] Using the gel material from Example 1.5, at room temperature, 2 / 3 of the magnesium oxide and water, along with all of the potassium dihydrogen phosphate, recycled stone powder, borax, and fiber, were first poured into a mixing pot and stirred for 1 minute. Then, the remaining magnesium oxide and water were added to the mixing pot and stirring continued for 1-2 minutes. Finally, the slurry was poured into a steel mold and allowed to stand for 28 days. This yielded a magnesium phosphate recycled inorganic cementitious material used for testing compressive and flexural strength.
[0074] The magnesium phosphate recycled inorganic cementitious material prepared in the example for testing compressive and flexural strength was injected into a 100mm×100mm×100mm steel mold, and its performance parameters were measured as follows: flowability 165-170mm, initial setting time 20-25min, final setting time 75-80min, initial compressive strength reaching 77.3-81.1MPa, and initial flexural strength 7.6-8.7MPa.
[0075] Example 2.6: A method for preparing a novel inorganic adhesive for filling joints in the repair of ancient buildings, specifically as follows:
[0076] Using the gel material from Example 1.6, at room temperature, 2 / 3 of the magnesium oxide and water, along with all of the potassium dihydrogen phosphate, recycled stone powder, borax, and fibers, were first poured into a mixing pot and stirred for 1 minute. Then, the remaining magnesium oxide and water were added to the mixing pot and stirring continued for 1-2 minutes. Finally, the slurry was poured into a steel mold and allowed to stand for 28 days. This yielded a magnesium phosphate recycled inorganic cementitious material for testing compressive and flexural strength.
[0077] The magnesium phosphate recycled inorganic cementitious material prepared in the example for testing compressive and flexural strength was injected into a 100mm×100mm×100mm steel mold. The measured performance parameters were as follows: fluidity 140-150mm (too low fluidity), initial setting time 15-20min, final setting time 100-110min (too long final setting time), initial compressive strength 65.3-67.2MPa, and initial flexural strength 4.3-4.8MPa.
[0078] Example 2.7: A method for preparing a novel inorganic adhesive for filling joints in the repair of ancient buildings, specifically as follows:
[0079] Using the gel material from Example 1.7, at room temperature, 2 / 3 of the magnesium oxide and water, along with all of the potassium dihydrogen phosphate, recycled stone powder, borax, and fiber, were first poured into a mixing pot and stirred for 1 minute. Then, the remaining magnesium oxide and water were added to the mixing pot and stirring continued for 1-2 minutes. Finally, the slurry was poured into a steel mold and allowed to stand for 28 days. This yielded a magnesium phosphate recycled inorganic cementitious material used for testing compressive and flexural strength.
[0080] The magnesium phosphate recycled inorganic cementitious material prepared in the example for testing compressive and flexural strength was injected into a 100mm×100mm×100mm steel mold. The measured performance parameters were as follows: fluidity 220-230mm (excessive fluidity), initial setting time 20-25min, final setting time 115-120min (excessive final setting time), initial compressive strength 55.6-61.7MPa (slightly low strength), and initial flexural strength 3.8-4.1MPa (slightly low strength).
[0081] Example 2.8: A method for preparing a novel inorganic adhesive for filling joints in the repair of ancient buildings, specifically as follows:
[0082] Using the gel material from Example 1.8, at room temperature, 2 / 3 of the magnesium oxide and water, along with all of the potassium dihydrogen phosphate, glutinous rice flour, borax, and fiber, were first poured into a mixing pot and stirred for 1 minute. Then, the remaining magnesium oxide and water were added to the mixing pot and stirring continued for 1-2 minutes. Finally, the slurry was poured into a steel mold and allowed to stand for 28 days. This yielded a magnesium phosphate recycled inorganic gelling material used for testing compressive and flexural strength.
[0083] The magnesium phosphate recycled inorganic cementitious material prepared in the example for testing compressive and flexural strength was injected into a 100mm×100mm×100mm steel mold. The measured performance parameters were as follows: fluidity 140-150mm (too low fluidity), initial setting time 35-40min, final setting time 100-110min (too long final setting time), initial compressive strength 67.4-70.4MPa, and initial flexural strength 3.1-3.9MPa.
[0084] Example 2.9: A method for preparing a novel inorganic adhesive for filling joints in the repair of ancient buildings, specifically as follows:
[0085] Using the gel material from Example 1.9, at room temperature, 2 / 3 of the magnesium oxide and water, along with all of the potassium dihydrogen phosphate, glutinous rice flour, borax, and fiber, were first poured into a mixing pot and stirred for 1 minute. Then, the remaining magnesium oxide and water were added to the mixing pot and stirring continued for 1-2 minutes. Finally, the slurry was poured into a steel mold and allowed to stand for 28 days. This yielded a magnesium phosphate recycled inorganic gelling material used for testing compressive and flexural strength.
[0086] The magnesium phosphate recycled inorganic cementitious material prepared in the example for testing compressive and flexural strength was injected into a 100mm×100mm×100mm steel mold. Its performance parameters were measured as follows: fluidity 140-150mm (too low fluidity), initial setting time 15-20min, final setting time 100-110min (too long final setting time), initial compressive strength 55.0-57.6MPa, and initial flexural strength 4.3-4.8MPa.
[0087] Example 2.10: A method for preparing a novel inorganic adhesive for filling joints in the repair of ancient buildings, specifically as follows:
[0088] Using the gel material from Example 1.10, at room temperature, 2 / 3 of the magnesium oxide and water, along with all of the potassium dihydrogen phosphate, glutinous rice flour, borax, and fiber, were first poured into a mixing pot and stirred for 1 minute. Then, the remaining magnesium oxide and water were added to the mixing pot and stirring continued for 1-2 minutes. Finally, the slurry was poured into a steel mold and allowed to stand for 28 days. This yielded a magnesium phosphate recycled inorganic gelling material used for testing compressive and flexural strength.
[0089] The magnesium phosphate recycled inorganic cementitious material prepared in the example for testing compressive and flexural strength was injected into a 100mm×100mm×100mm steel mold. The measured performance parameters were: flowability 160-170mm, initial setting time 20-25min, final setting time 100-110min (if the final setting time is too long), initial compressive strength 39.4-40.9MPa, and initial flexural strength 4.0-5.1MPa.
[0090] Example 2.11: A method for preparing a novel inorganic adhesive for filling joints in the repair of ancient buildings, specifically as follows:
[0091] Using the gel material from Example 1.11, at room temperature, 2 / 3 of the magnesium oxide and water, along with all of the potassium dihydrogen phosphate, glutinous rice flour, borax, and fiber, were first poured into a mixing pot and stirred for 1 minute. Then, the remaining magnesium oxide and water were added to the mixing pot and stirring continued for 1-2 minutes. Finally, the slurry was poured into a steel mold and allowed to stand for 28 days. This yielded a magnesium phosphate recycled inorganic gelling material used for testing compressive and flexural strength.
[0092] The magnesium phosphate recycled inorganic cementitious material prepared in the example for testing compressive and flexural strength was injected into a 100mm×100mm×100mm steel mold, and its performance parameters were measured as follows: flowability 150-160mm, initial setting time 25-30min, final setting time 95-105min, initial compressive strength reaching 71.5-82.6MPa, and initial flexural strength 8.1-8.7MPa.
[0093] Example 2.12: A method for preparing a novel inorganic adhesive for filling joints in the repair of ancient buildings, specifically as follows:
[0094] Using the gel material from Example 1.12, at room temperature, 2 / 3 of the magnesium oxide and water, along with all of the potassium dihydrogen phosphate, glutinous rice flour, borax, and fiber, were first poured into a mixing pot and stirred for 1 minute. Then, the remaining magnesium oxide and water were added to the mixing pot and stirring continued for 1-2 minutes. Finally, the slurry was poured into a steel mold and allowed to stand for 28 days. This yielded a magnesium phosphate recycled inorganic gelling material used for testing compressive and flexural strength.
[0095] The magnesium phosphate recycled inorganic cementitious material prepared in the example for testing compressive and flexural strength was injected into a 100mm×100mm×100mm steel mold. Its performance parameters were measured as follows: fluidity 150-160mm, initial setting time 25-30min, final setting time 100-110min (if the final setting time is too long), initial compressive strength 70.5-77.6MPa, and initial flexural strength 7.8-8.1MPa.
[0096] Example 2.13: A method for preparing a novel inorganic adhesive for filling joints in the repair of ancient buildings, specifically as follows:
[0097] Using the gel material from Example 1.13, at room temperature, 2 / 3 of the magnesium oxide and water, along with all of the potassium dihydrogen phosphate, glutinous rice flour, borax, and fiber, were first poured into a mixing pot and stirred for 1 minute. Then, the remaining magnesium oxide and water were added to the mixing pot and stirring continued for 1-2 minutes. Finally, the slurry was poured into a steel mold and allowed to stand for 28 days. This yielded a magnesium phosphate recycled inorganic gelling material used for testing compressive and flexural strength.
[0098] The magnesium phosphate recycled inorganic cementitious material prepared in the example for testing compressive and flexural strength was injected into a 100mm×100mm×100mm steel mold. Its performance parameters were measured as follows: fluidity 140-150mm (too low fluidity), initial setting time 30-35min, final setting time 100-110min (too long final setting time), initial compressive strength 61.9-66.6MPa, and initial flexural strength 3.8-4.3MPa.
[0099] Example 2.14: A method for preparing a novel inorganic adhesive for filling joints in the repair of ancient buildings, specifically as follows:
[0100] Using the gel material from Example 1.14, at room temperature, 2 / 3 of the magnesium oxide and water, along with all of the potassium dihydrogen phosphate, borax, and fibers, were first poured into a mixing pot and stirred for 1 minute. Then, the remaining magnesium oxide and water were added to the mixing pot and stirring continued for 1-2 minutes. Finally, the slurry was poured into a steel mold and allowed to stand for 28 days. This yielded a magnesium phosphate recycled inorganic gelling material used for testing compressive and flexural strength.
[0101] The magnesium phosphate recycled inorganic cementitious material prepared in the example for testing compressive and flexural strength was injected into a 100mm×100mm×100mm steel mold, and its performance parameters were measured as follows: flowability 150-160mm, initial setting time 30-40min, final setting time 90-100min, initial compressive strength reaching 80.7-83.1MPa, and initial flexural strength 11.3-12.1MPa.
[0102] This invention is not limited to the embodiments described above. Anyone should understand that structural changes made under the guidance of this invention, and any technical solutions that are the same as or similar to this invention, fall within the protection scope of this invention. Technical aspects, shapes, and structures not described in detail in this invention are all publicly known technologies.
Claims
1. A new type of inorganic glue for repairing and filling seams of ancient buildings, characterized in that: The composition comprises the following parts by weight: 30-48 parts of dead-burned magnesium oxide, 20-30 parts of potassium dihydrogen phosphate, 2-6 parts of borax, 6-24 parts of fine aggregate, 3-8 parts of basalt fiber, 5-15 parts of glutinous rice flour, and 15-20 parts of water.
2. A novel inorganic adhesive for repairing and filling seams of ancient buildings according to claim 1, characterized in that: Dead-burned magnesium oxide is a mixture of one or more of MgO, Al2O3, Fe2O3, CaO, SO2, TiO2, Na2O, and SO3.
3. A novel inorganic glue for repairing and filling seams of ancient buildings according to claim 2, characterized in that: The fine aggregate is made by mixing recycled fine aggregate with a particle size of 2-5 mm and expanded clay in a mass ratio of 2.8-3.7:2.2-3.
1.
4. The novel inorganic adhesive for repairing and filling seams of ancient buildings according to claim 3 is characterized in that: The recycled fine aggregate is one of glass powder, recycled stone powder, recycled brick powder and recycled cement; wherein the recycled stone powder is a powder with a fineness of 600-700 mesh obtained by grinding and sieving recycled stone powder.
5. A method for preparing a novel inorganic adhesive for repairing and filling seams of ancient buildings, characterized in that: The following steps are involved: Step 1: Weigh various materials according to the raw material ratio, then pour potassium dihydrogen phosphate, fine aggregate, glutinous rice flour, basalt fiber and borax into a cement mortar mixer and dry mix for 0.5-2 minutes, then slowly add 1 / 3-3 / 4 of the total water and continue stirring to obtain a uniform slurry; Step 2: then add the dead-burned magnesium oxide and the remaining 1 / 4-2 / 3 of water and stir rapidly for 3-4 minutes before discharging to obtain magnesium phosphate regenerated inorganic glue.
6. The method for preparing a novel inorganic adhesive for repairing and filling seams of ancient buildings according to claim 5, characterized in that: In step 1, the preparation of potassium dihydrogen phosphate is specifically as follows: first, 4-8 mol / L phosphoric acid is added into a round-bottom flask, then 200-300 ml of 4-8 mol / L potassium hydroxide is poured into the flask through drainage with a glass rod, and the mixture is heated under reflux at a temperature of 300-500° C. to generate a precipitate, and then the precipitate is filtered to concentrate the filtrate to a relative density of 1.3-1.35, and the mixture is cooled, and crystals are filtered out by suction, and then the crystals are washed with ionized water, and potassium dihydrogen phosphate is obtained after drying.
7. The method for preparing a novel inorganic adhesive for repairing and filling seams of ancient buildings according to claim 5, characterized in that: In step 1, the preparation of basalt fiber is specifically as follows: 10-15g of basalt stone is placed in a calcining furnace, placed at a temperature of 1450℃-1500℃ for 5-15min, and after the basalt stone is melted, it is drawn at high speed using a platinum-rhodium alloy bushing to obtain continuous basalt fiber.
8. The method for preparing a novel inorganic adhesive for repairing and filling seams of ancient buildings according to claim 5, characterized in that: In step 1, the preparation of glutinous rice flour is specifically as follows: first, 20-40 g of glutinous rice is put into a grinder, first rotated forward for 20-40 minutes, then reversed for 20-40 minutes to obtain glutinous rice flour, and finally passed through a 80-100 mesh sieve to obtain glutinous rice flour.
9. The method for preparing a novel inorganic adhesive for repairing and filling seams of ancient buildings according to claim 5, characterized in that: In step 2, the preparation of dead-burned magnesium oxide is specifically to first place the dolomite in a kiln and calcine it at a high temperature of 1500-1900°C, then grind the calcined material into brown-yellow granular materials of different particle sizes, and then sieve to retain the powder with a particle size of ≤15mm to obtain dead-burned magnesium oxide.
10. The method for preparing a novel inorganic adhesive for repairing and filling seams of ancient buildings according to claim 5, characterized in that: Magnesite is a mineral with MgCO3 as the main component, with mud content ≤0.83%, mud block content ≤0.4%, solidity index ≤10.0%, light material content ≤1.0%, and sulfide and sulfate content ≤1.0%.
Citation Information
Cited By
Magnesium phosphate inorganic adhesive as well as preparation method and application thereof
CN120505044A